Comprehensive Neuropsychiatric and Cognitive Characterization of Former Professional Football Players: Implications for Neurorehabilitation - Terpstra, Alex R.; Vasquez, Brandon P.; Colella, Brenda; Tartaglia, Maria Carmela; Tator, Charles H.; Mikulis, David; Davis, Karen D.; Wennberg, Richard; Green, Robin E. A. (Frontiers in Neurology, 2019)
Objectives: With the overarching aim of identifying novel targets for neurorehabilitation, our objectives were to: (1) comprehensively characterize neuropsychiatric and cognitive functioning in high-functioning former professional football players with a focus on executive functioning; (2) distinguish concussion-related impairments from cohort characteristics unique to elite professional football players; and, (3) explore the relationship between executive function and neuropsychiatric impairments in this population. Participants: 61 high-functioning former professional football players and 31 age- and sex-matched control participants without history of concussion or participation in contact sports. Design: Between-groups analysis. Main measures: Neuropsychiatric. Personality Assessment Inventory (PAI) clinical scales plus the Aggression treatment consideration scale; the Mini International Neuropsychiatric Interview (MINI). Cognitive. Comprehensive clinical neuropsychological battery assessing domains of verbal and visuospatial attention, speed of processing and memory; current and estimated pre-morbid IQ; and, executive functioning, including two novel measures for this population (i.e., response inhibition and intra-individual variability [IIV], a measure of consistency in responding). Results: (1) Compared to control participants, former professional football players scored significantly higher on the PAI’s Depression, Mania, and Aggression scales, and significantly lower on response inhibition. (2) Retired players with a higher concussion history (4 or more concussions; x̅=6.1), but not retired players with a lower concussion history (3 or fewer concussions; x̅=2.0), showed (i) significantly higher scores on the Depression scale, (ii) more MINI diagnoses overall and manic/hypomanic episodes specifically, and (iii) poorer executive function than control participants. (3) The relationships between concussion exposure and, (i) the PAI Mania scale and (ii) the PAI Aggression scale, respectively, were fully mediated by IIV; Depression on the PAI was partially mediated by IIV. Conclusions: In high-functioning former professional football players, impairments were observed in several neuropsychiatric domains and on experimental measures of executive function. Many findings were attributable to concussion history rather than to cohort characteristics. As inconsistency of responding) mediated relationships between concussion exposure and Mania, Aggression, and Depression (partially), it warrants further investigation; if it does increase vulnerability to expression of neuropsychiatric symptoms in individuals with a history of multiple concussions, this would constitute a novel and important treatment target.